Heterogeneous responses of firms to trade protection - Konings, Jozef; Vandenbussche, Hylke (Centre for Economic Policy Research, 2008)
This paper uses EU firm-level panel data to estimate the effect of Antidumping (AD) protection on the productivity of EU domestic firms in import-competing industries. We find that firms with relatively low initial productivity - laggard firms - have productivity gains during AD protection, while firms with high initial productivity - frontier firms - experience productivity losses. While the productivity of the average firm is moderately improved during AD protection, productivity remains below that of firms never involved in AD cases, thus questioning the desirability of protection. Our empirical results are consistent with recent theoretical work supporting the view that trade policy can have a differential effect on firms depending on their initial productivity.
International trade and regional economics
Keywords: antidumping protection; firm heterogeneity; total factor productivity; Research Subject Categories::SOCIAL SCIENCES::Business and economics